Improvement of yield of the edible and medicinal mushroom Lentinula edodes on wheat straw by use of supplemented spawn - Gaitán-Hernández, Rigoberto (Sociedade Brasileira de Microbiologia, 2014)
The research evaluated the interactions of two main factors (strain / types of spawn) on various parameters with the purpose to assess its effect on yield and biochemical composition of Lentinula edodes fruiting bodies cultivated on pasteurized wheat straw. The evaluation was made with four strains (IE-40, IE-105, IE-124 and IE-256). Different types of spawns were prepared: Control (C) (millet seed, 100%), F1 (millet seed, 88.5%; wheat bran, 8.8%; peat moss, 1.3%; and CaS0(4), 1.3%) and F2 (the same formula as F1, but substituting the wheat bran with powdered wheat straw). Wheat straw was pasteurized by soaking it for 1 h in water heated to 65 °C. After this the substrate (2 kg wet weight) was placed in polypropylene bags. The bags were inoculated with each spawn (5% w/w) and incubated in a dark room at 25 °C. A proximate analysis of mature fruiting bodies was conducted. The mean Biological Efficiency (BE) varied between 66.0% (C-IE-256) and 320.1% (F1-IE-124), with an average per strain of 125.6%. The highest mean BE was observed on spawn F1 (188.3%), significantly different from C and F2. The protein content of fruiting bodies was high, particularly in strain IE-40-F1 (17.7%). The amount of fat varied from 1.1 (F1-IE-40) to 2.1% (F2-IE-105) on dry matter. Carbohydrates ranged from 58.8% (F1-IE-40) to 66.1% (F1-IE-256). The energy value determined ranged from 302.9 kcal (F1-IE-40) to 332.0 kcal (F1-IE-256). The variability on BE observed in this study was significantly influenced by the spawn’s formulation and genetic factors of the different strains.